Implications of food aid for price policy in recipient countries - von Braun, Joachim; Huddleston, Barbara (International Food Policy Research Institute, 1988)
Although it is widely believed that food aid distorts incentives to increase agricultural production, detailed empirical country studies conducted in recent years suggest that the disincentive effect of food aid has been overemphasized. An analysis of sixteen developing countries that achieved particularly high growth rates in food production of 3.9 percent during 1961-76 shows that they also received about 80 percent more food aid per capita than the average food aid recipient country.1 Six of these countries were receiving an especially high amount of food aid over an extended period. While there is no clear-cut negative or positive relationship between food aid and growth in food production, they are not mutually exclusive. Government policy plays a crucial role in this regard.